2019
DOI: 10.1128/aem.01226-19
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Atf1 Regulates Expression of Cellulase and Xylanase Genes during Solid-State Fermentation of Ascomycetes

Abstract: Transcriptional regulation of cellulolytic and xylolytic genes in ascomycete fungi is controlled by specific carbon sources in different external environments. Here, comparative transcriptomic analyses of Penicillium oxalicum grown on wheat bran (WB), WB plus rice straw (WR), or WB plus Avicel (WA) as the sole carbon source under solid-state fermentation (SSF) revealed that most of the differentially expressed genes (DEGs) were involved in metabolism, specifically, carbohydrate metabolism. Of the DEGs, the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Combination of Fusarium sp. ZH-H2 and starch offers a suitable alternative for bioremediation of aged polycyclic aromatic hydrocarbon (PAH)-contaminated soil in coal mining areas ( Zhao et al, 2019 ).…”
Section: Species Diversity Of Filamentous Fungi Used In Pollutant Rem...mentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of Fusarium sp. ZH-H2 and starch offers a suitable alternative for bioremediation of aged polycyclic aromatic hydrocarbon (PAH)-contaminated soil in coal mining areas ( Zhao et al, 2019 ).…”
Section: Species Diversity Of Filamentous Fungi Used In Pollutant Rem...mentioning
confidence: 99%
“…Overexpression of mutated AraR in Penicillium oxalicum lead to constitutive production of α-L-arabinofuranosidase ( Gao et al, 2019 ). Deletion of the regulatory gene Atf1 increased cellulase and xylanase production in P. oxalicum ( Zhao et al, 2019 ). Deletion of repressors SxlR and Rce1 in Trichoderma reesei significantly stimulated xylanase ( Liu et al, 2017 ) and cellulase ( Cao et al, 2017 ) activities, respectively.…”
Section: Fungal Byproduct Recoverymentioning
confidence: 99%
“…ATF1 has been shown to play an important role in cell proliferation, differentiation and apoptosis [ 27 ]. ATF1, as a regulator, also promoting sexual differentiation and entry into the stationary phase in S. pombe [ 28 ]. AtfA and Atf1 are quite highly conserved and that they are involved in multiple cellular processes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATF1, as a regulator, also promoting sexual differentiation and entry into the stationary phase in S. pombe [ 28 ]. AtfA and Atf1 are quite highly conserved and that they are involved in multiple cellular processes [ 28 ]. In this study, we found that overexpression of ATF1 partially reversed the promotion effects of miR-589-3p on osteogenic differentiation of PDLSCs.…”
Section: Discussionmentioning
confidence: 99%
“…They allow moderate expression of cellulase and xylanase genes in T. reesei ( cbh2 and xyn2 ) [ 109 ] Lae1 and VELVET complex In T. reesei (LaeA orthologue in A. nidulans ), it act as a methyltransferase induces cellulase expression and forming the VELVET complex, which in turn regulates the transcription of major cellulase genes [ 110 ] PacC/Pac1 In A. nidulans and T. reesei , it respond to pH variance in the external environment, stimulate or prevent cellulase production. At neutral pH, the abolition of the pac1 gene increases Xyr1 activity [ 5 , 55 ] PoxMBF1 In Penicillium oxalicum , it binds directly to the promoter regions of principal cellulase and xylanase genes to induce cellulase production [ 111 ] PoxFlbC In Penicillium oxalicum (FlbC orthologue in Aspergillus ), it upregulates most of the cellulase genes [ 112 ] PoxAtf1 In filamentous fungi, it controls the expression of cellulase and xylanase genes during the solid-state fermentation [ 113 ] Blr1, Blr2, and Env1 Photoreceptor proteins (Blr1, Blr2, and Env1) in both light and dark regulate the cellulase gene from T. reesei . The photoreceptor regulative mechanism of carbon metabolism in T. reesei is dependent on Blr1 and Blr2 controlled by the Env1 photoreceptor [ 114 ] Seb1 In Talaromyces pinophilus EMU, Seb1 transcription factor binds to the stress response element (STRE) and CRISPR-Cas9 mediated degradation of seb1 gene led to the 20–40% increment in FPase activity [ 123 ] TrAZF1 In T. reesei and A. nidulans positively regulates the activity of BGL and CBH by interacting with the cel7a, cel45a , and sow promoter region [ 115 ] …”
Section: Molecular Mechanisms Behind the Cellulase Expressionmentioning
confidence: 99%